Pengaruh Budaya Organisasi dan Komunikasi Organisasi terhadap Kinerja Karyawan PT. X - Jujung Dwi Marta; Dewie Tri Wijayati (Universitas Negeri Surabaya, 2018)
The purpose of this study was to analyze the influence of organizational culture and communication organizations on employee performance. Samples of this study was sampled every part of the whole section in the PT. X Surabaya which numbered 80 from a population of 500. The data analysis technique used is multiple linear regression analysis with SPSS 20 software.